2000
DOI: 10.1177/089198870001300403
|View full text |Cite
|
Sign up to set email alerts
|

Review of Outcome Measurement Instruments in Alzheimer's Disease Drug Trials: Psychometric Properties of Behavior and Mood Scales

Abstract: This article reviews the reliability and validity of eight scales for behavior and mood problems that were identified in a comparative analysis of Alzheimer's disease (AD) drug trials. The scales are the Brief Psychiatric Rating Scale, the Alzheimer's Disease Assessment Scale-noncognitive, the Relative's Assessment of Global Symptomatology, the Consortium to Establish a Registry for Alzheimer's Disease-Behavior Rating Scale for Dementia, the Dementia Behavior Disturbance scale, the Neuropsychiatric Inventory, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 68 publications
0
53
0
Order By: Relevance
“…Later versions of the inventory, used in studies not reviewed, were translated into several languages. While the Neuropsychiatric Inventory is popular worldwide it has been criticized for not being responsive to change and score distributions (Perrault et al, 2000). Two of the 4 studies using the Neuropsychiatric Inventory, both conducted by Raglio et al (2008Raglio et al ( , 2010, showed significant decreases in anxiety scores: 3.34-2.93 (p = 0.002) and 2.63-0.93 (p < 0.001) (Raglio et al, 2008(Raglio et al, , 2010.…”
Section: Reliability and Validity Of The Measuresmentioning
confidence: 99%
“…Later versions of the inventory, used in studies not reviewed, were translated into several languages. While the Neuropsychiatric Inventory is popular worldwide it has been criticized for not being responsive to change and score distributions (Perrault et al, 2000). Two of the 4 studies using the Neuropsychiatric Inventory, both conducted by Raglio et al (2008Raglio et al ( , 2010, showed significant decreases in anxiety scores: 3.34-2.93 (p = 0.002) and 2.63-0.93 (p < 0.001) (Raglio et al, 2008(Raglio et al, , 2010.…”
Section: Reliability and Validity Of The Measuresmentioning
confidence: 99%
“…0.79 for frequency and 0.86 for severity) and good inter-rater reliability had been established (e.g. 84.1%À100% crude agreement) (Perrault et al, 2000). Folstein, & McHugh, 1975).…”
Section: Data Collectionmentioning
confidence: 99%
“…Moreover, patients undergoing cholinergic drug treatments have shown changes in mood (28). We therefore examined psychiatric-like behaviors in VAChT Six3-Cre-flox/flox mice.…”
Section: Forebrain Cholinergic Tone Is Involved In Spontaneous Locomomentioning
confidence: 99%